Mendelian randomization integrating GWAS and eQTL data reveals genetic determinants of complex and clinical traits - Eleonora Porcu (Nature Portfolio, 2019)
Many genetic variants identified in genome-wide association studies are associated with gene expression. Here, Porcu et al. propose a transcriptome-wide summary statistics-based Mendelian randomization approach (TWMR) that, applied to 43 human traits, uncovers hundreds of previously unreported gene–trait associations.